فاعلية نظام مساعد للتنقل باستخدام وحدة إظهار حسية من وجهة نظر المكفوفين لدى عينة من الطلبة المكفوفين في جامعة دمشق - أبو النور، حسن; العلاوي، ماهر (جامعه دمشق - كليه التربية, 2022)
تهدف هذه الدراسة إلى معرفة مدى فاعلية نظام مساعد للمكفوفين في كشف العوائق المحيطة بهم، وكذلك قياس مدى تكيفهم معه، والتعرف على آرائهم حول تصميمه، لدى عينة من طلبة جامعة دمشق المكفوفين، والمقيمين في المدينة الجامعية، تكونت عينة الدراسة من (۳۲) طالبا وطالبة، منهم (۱۷) طالبا و(١٥) طالبة. قام الباحث بتصميم نظام مساعدة إلكترونية، لمساعدة المكفوفين في الكشف المكاني للعوائق، حيث قام الباحث بتدريب أفراد العينة بشكل كاف على نظام المساعدة. كما تم تصميم أداة للتعرف على مدى فاعلية نظام المساعدة للمكفوفين في التنقل، باستخدام وحدة الإظهار، واستخرج الخصائص السيكومترية للصدق، والثبات. وأسفرت الدراسة عن نتائج، من أهمها: وجود مستوى كبير في فاعلية نظام مساعد للمكفوفين في كشف العوائق، وبمستوى مرتفع في مدى القدرة على الكشف المكاني للعوائق بشكل عام، لدى الطلبة المكفوفين، أفراد عينة البحث، وبالمثل في مدى تكيف الكفيف مع نظام المساعدة، بمستوى جيد في درجات تقدير تصميم وحدة الإظهار الحسية، من وجهة نظر المكفوفين، أفراد عينة البحث. كما كشفت الدراسة بالإضافة إلى ذلك، وجود علاقة إيجابية دالة، بين مدى فاعلية نظام المساعدة في الكشف المكاني عن العوائق، وتكيف الكفيف مع النظام، لدى المكفوفين، وكذلك الأمر، بين مدى فاعلية الكشف المكاني للعوائق، وتصميم وحدة الإظهار الحسية، وبينت النتائج وجود فروق دالة إحصائيا، بين متوسط درجات الذكور، ومتوسط درجات الإناث، لصالح الذكور في فاعلية نظام مساعد للتنقل، باستخدام وحدة إظهار حسية، من وجهة نظر المكفوفين. This study aims to find out how effective assistant for the blind system to detect their surroundings barriers, as well as measure how they adjust with him, and get to know their opinions how well designed, among a sample of the University of Damascus blind students, and residents of the university student house. The study sample consisted of (32) male and female students, including 17 students and 15 female students. The researcher has designed an electronic system to help to assist the blind in the spatial detection of obstacles. The researcher trained them sufficiently on the system. as a tool was designed to identify the effectiveness of the assistance system for the blind to navigate using the show honesty and account transactions, the necessary stability. The study concluded in the results, including: the presence of a high level in the extent of the ability to spatial detection of obstacles. In general, the students are blind sample individuals, as well as up, in the extent of adaptation of the blind with the aid system, a good level in the ratings of module design Manifesting sensory from the point eyes blind research sample. The study revealed as well as the presence of a function is a positive relationship between the effectiveness of the aid system in the spatial detection of obstacles and adapt to the blind with the system with the blind, as well as the matter of how effective spatial detection of obstacles and module design Manifesting sensual, and the results showed the presence of statistically significant differences between mean scores male, female, and the average grades, in favor of males in the effectiveness of assistant system to navigate using the sensory show from the perspective of the blind.
Keywords: البرامج الناطقة -- الإعاقة البصرية -- مهارات الحاسوب -- المساعدات الاجتماعية